Robert N. Butler, MD : visionary of healthy aging - Achenbaum, W. Andrew (Columbia University Press, 2013)
Robert Neil Butler (1927?2010) was a scholar, psychiatrist, and Pulitzer Prize-winning author who revolutionized the way the world thinks about aging. One of the first psychiatrists to engage with older men and women outside of institutional settings, Butler coined the term?ageism" to draw attention to discrimination against older adults and spent a lifetime working to improve their status, medical treatment, and care. Early in his career, Butler seized on the positive features of late-life development?aspects he documented in his pathbreaking research on?healthy aging" at the Na.